A survey on the industry’s perception of digital twins – a follow-up to the digital twin workshop at the DESIGN Conference 2022 - Fett, Michel; Zwickler, Julius; Wilking, Fabian; Götz, Stefan; Schweigert-Recksiek, Sebastian; Hicks, Ben; Nespoli, Oscar; Wärmefjord, Kristina; Wartzack, Sandro; Kirchner, Eckhard (Proceedings of the Design Society, 2024)
Digital Twins are perceived differently between and within industry and academia regarding applications and potentials. For this reason, a round table was formed based on the Digital Twin Workshop of the Design Conference 2022. One of the results of this round table is this contribution, which deals with a survey within the industry. The survey captured the understanding of the different roles in the creation and use of Digital Twins, the requirements and hurdles as well as the perception of methodological support. In addition, factors that influence the perception were identified.
CRIS-Team Scopus Importer:2024-05-31
Keywords: design workshop; digital twin; industry 4.0; survey